Wideband circular polarization selective surface - Yang, Lingtong (Nanyang Technological University, 2023)
Circular Polarization Selection Surface (CPSS) plays an important role in wireless communications, especially in satellite communications. However, the operating frequency bandwidth of most existing designs is too narrow, which makes it limited application. In this thesis, current research on CPSS is discussed and summarized, and a novel structure based on the double meandered arm structure is proposed. The main contents and innovations of this thesis are as follows: (1) According to the current research, three structures: Pierrot structure, Tilston’s structure, and cascaded structure are discussed and analyzed. This thesis summarizes the advantages and disadvantages of these three structure, choosing Pierrot structure as the main research direction. (2) This thesis verifies the feasibility and reliability of Pierrot structure for CPSS, reproducing a traditional Pierrot structure in CST and HFSS and confirming the validity of the simulations conducted. (3) Based on the invesitigation for widening the operating bandwidth, the fan-like structure and meandered arm structure are proposed and simulated. As a result, a double meandered arm structure has better performance. Its relative bandwidth is 10.26-11.00 GHz (6.98%), which is more than 5% higher than the bandwidth of the traditional structure of 1.66%. (4) On the basis of the fan-like structure and meandered arm structure, this thesis proposes a novel double-arm meandered arm structure and further widens the bandwidth to 12.04%. Additionally, the insertion loss (IL) meets the requirement of the novel CPSS design.